2017
DOI: 10.1128/aac.01092-16
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Doxycycline in the Treatment of Syphilis

Abstract: Doxycycline is an alternative antibiotic drug for the treatment of syphilis, but data on its efficacy, especially data on its efficacy against late latent syphilis, are limited. A retrospective study was conducted to evaluate the effectiveness of doxycycline for the treatment of patients with different stages of syphilis. Patients who received doxycycline treatment between June 2011 and June 2014 were involved. The serological response to doxycycline was defined as either a negative toluidine red unheated seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…MMPs are known to associate with several pathological conditions, such as rheumatoid arthritis, tumor invasion, multiple sclerosis (Marten and Zhou, 2005), syphlis (Dai et al, 2017), cardiovascular, neurological, and skin disorder (Griffin et al, 2010). MMPs are a family of zinc endopeptidases that play a vital role in interaction between viral protein and host receptor and fusion (Phillips et al, 2017), degrade proteins of extracellular matrix leading to production of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are known to associate with several pathological conditions, such as rheumatoid arthritis, tumor invasion, multiple sclerosis (Marten and Zhou, 2005), syphlis (Dai et al, 2017), cardiovascular, neurological, and skin disorder (Griffin et al, 2010). MMPs are a family of zinc endopeptidases that play a vital role in interaction between viral protein and host receptor and fusion (Phillips et al, 2017), degrade proteins of extracellular matrix leading to production of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The European syphilis management guideline recommends intramuscular procaine penicillin for 10–14 days as second-line therapy option if benzathine penicillin G is not available with additional options, such as doxycycline, ceftriaxone or azithromycin, in case of bleeding disorders, penicillin allergy or refusal of parenteral treatment [44]. All three alternatives are effective; however, a recent meta-analysis found that doxycycline/tetracycline recipients had a higher treatment failure rate than those treated with benzathine penicillin G [4650]. In addition, azithromycin resistance and treatment failures have been described in the USA, Europe, Australia, China and elsewhere and azithromycin should therefore only be used as a last resort and when treatment can be followed up closely [6, 44, 51].…”
Section: Syphilis Treatmentmentioning
confidence: 99%
“…However, only three randomized clinical trials have compared penicillin to other antibiotics (i.e., ceftriaxone and azithromycin) [20] , [21] , [22] . Conversely, the efficacy of doxycycline, the second-line treatment for syphilis, is mainly supported by two prospective studies [ 23 , 24 ] and other small retrospective studies [25] , [26] , [27] .…”
Section: Introductionmentioning
confidence: 99%